ANALISIS PERILAKU KONSUMEN PADA BIRO PERJALANAN WISATA BERBASIS SOPHISTICATION DI KOTA MAKASSAR DAN LOMBOK - Djabbar, Atriana; Amirullah, Amirullah; Maryati, Sri (Universitas Hasanuddin, 2024)
The study aims to analyze consumer behavior on sophistication-based travel agencies in the cities of Makassar and Lombok. The research method used is qualitative descriptive with both quantitative and qualitational approaches. Data collection is done through interviews, observations, questionnaires, document studies, and focus group discussions. The findings show several trends and patterns of consumer behavior in the travel industry, including: increased use of digital technology, preference for meaningful and sustainable travel experiences, personalization of technology-based services, flexibility in travel planning, and search for unique and authentic experiences. The travel components that tourists mainly consider include transportation, accommodation, tourist attractions, food facilities, and gourmet shops. This research provides insight into the development of marketing strategies and preparation of maritime tour packages that match the current trends and consumer preferences.